2005
DOI: 10.1111/j.1368-5031.2005.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Varicose veins arising from the pelvis due to ovarian vein incompetence

Abstract: Vulval varices and perivulval veins are common though often unrecognised, and pelvic pain is a common complaint, sometimes without an obvious cause, hence treatment is not always successful. An association between these two problems has long been established, and some cases of pelvic pain are clearly associated with venous pathology. Often, these patients present to the vein clinic with recurrent varicose veins, because the standard procedures have failed and the pelvic origin was not recognised. The understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 17 publications
0
73
0
1
Order By: Relevance
“…They may be the consequence of chronic pelvic congestion, portal hypertension or obstructive pelvic lesions. Ovarian vein incompetence can lead to varicosities in the vulva and legs (Hobbs 2005).…”
Section: Varicose Veinsmentioning
confidence: 99%
“…They may be the consequence of chronic pelvic congestion, portal hypertension or obstructive pelvic lesions. Ovarian vein incompetence can lead to varicosities in the vulva and legs (Hobbs 2005).…”
Section: Varicose Veinsmentioning
confidence: 99%
“…Unilateral or bilateral ovarian vein incompetence can cause pelvic congestion syndrome, which induces chronic pain, irritable bladder, dysfunction of the pelvic organs, or vulval varices and varicose veins in the lower limbs (1,5,7). Our previous study demonstrated that chronic prostatitis and stress urinary incontinence were related to the existence of vena cava reflux caused by tricuspid regurgitation (28).…”
mentioning
confidence: 99%
“…If the symptoms persist for more than 12 weeks postpartum, the varix can be treated with sclerotherapy [10]. Although in some mild cases successful treatment can be achieved with either local excision or sclerotherapy [5,6,10,11], a laparoscopic ligation of the incompetent veins can be considered in patients with pelvic congestion syndrome [11]. In the author's case, the patient's vaginal varix resolved after 6 weeks postpartum without any additional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient recognized the lesion growing in the later months of gestation. Most genital varices are asymptomatic, but a few are associated with severe local discomfort, accompanied by spontaneous vaginal bleeding, or with pelvic pain as part of the so-called "pelvic congestion syndrome"; pelvic pain, dyspareuria, dysmenorrhea, dysuria, vulvar and perivulvar varices [5,6]. The vaginal varix can be ruptured from trauma, leading to a vaginal hematoma or thrombus during the second stage of labor.…”
Section: Discussionmentioning
confidence: 99%